History and the debate over intellectual property - Peng, Mike; Ahlstrom, D.; Carraher, S.; Shi, W. (2017)
This article responds to recent calls for organizational research to address larger, more globally relevant questions and to pay attention to history, by analyzing the crucial debate over intellectual property rights (IPR) between the United States and China. Despite the recent US position, the United States has not always been a leading IPR advocate. Rather, it was a leading IPR violator during the nineteenth century. An institution-based view of IPR history suggests that both the US refusal to protect foreign IPR in the nineteenth century and the current Chinese lack of enthusiasm to meet US IPR demands represent rational choices. However, as cost-benefit considerations change institutional transitions are possible. We predict that to the same extent the United States voluntarily agreed to strengthen IPR protection when its economy became sufficiently innovation-driven, China will similarly improve its IPR protection.